PARADIGM-HF: Disease Progression Slowed with Novel Drug - Mosley, Mary (MD Conference Express, 2014)
LCZ696 significantly reduced the composite primary outcome of cardiovascular death or heart failure (HF) hospitalization in patients with HF and reduced ejection fraction in the prospective trial Efficacy and Safety of LCZ696 Compared With Enalapril on Morbidity and Mortality of Patients With Chronic Heart Failure [PARADIGM-HF. New results from analyses of prespecified outcomes showed that HF progression is attenuated and fatal and that nonfatal worsening HF is delayed or prevented with LCZ696 when compared with enalapril, as discussed in this article.